The Insight Effectiveness of the Nearby Bitcoin Futures’ Hedging under Hedging Ratio Analysis - Asvathitanont , Chayakrit; Buranasiri, Jiroj (Business Administration and Management Journal Review, 2023)
The study aims at finding the usefulness and the effectiveness of the use of Bitcoin futures for Bitcoin hedging. The daily returns of Bitcoin and its nearby futures from March 28, 2018 to December 28, 2019 are collected for the investigation. The graph and correlation of Bitcoin and its futures’ returns show their strong association and the promised potentiality of Bitcoin futures to be used as hedging instruments. The analysis of the hedged portfolios under ordinary least squares regression model (OLS), vector autoregressive model (VAR), and vector error correction model (VECM) hedge ratios demonstrate superior performances over the unhedged portfolio concerning risk reduction and reward to risk holding. However, using different hedge ratios result different performances since OLS technique considers only the relationship of spot and futures data in the same periods, VAR counts the relationship of spot and lag variables of itself and of the futures in the short-run, and VECM takes the long-run cointegration between spot and futures into consideration. The concern of more profound relationship in VAR and VECM does not improve risk reduction. The statistical result shows that OLS hedged portfolio has the lowest risk. Nevertheless, VAR hedged portfolio offers higher reward to risk.